America's "Whiz Kids"? Ambivalence and the Model Minority Stereotype. Issue 2 (4th March 2019) - Ball, Daisy
Abstract: Asian Americans are commonly stereotyped as the "model minority": smart, diligent, quiet, and conformist. While at the outset the model minority stereotype appears to be positive, consensus in academia is that this stereotype has significant negative consequences for those to whom it is applied. Moreover, the literature has repeatedly documented that the model minority stereotype is largely unfounded—that is, the model minority is a myth. The present study employs in-depth interviews with Asian American college students to gauge campus climate. Respondents tell dual tales: they reject the assumption that Asian Americans are the model minority while lending significant support for it via their narratives. Elements of the model minority stereotype are repeatedly invoked as respondents paint highly positive portraits of themselves. While the negative implications of the model minority stereotype are acknowledged, the possibility that this stereotype serves largely positive functions—for some Asian Americans—is considered, thereby adding much-needed nuance to the debate surrounding the model minority stereotype.